2009
DOI: 10.1021/es802841x
|View full text |Cite
|
Sign up to set email alerts
|

Natural Attenuation of Arsenic by Sediment Sorption and Oxidation

Abstract: Arsenic sorption onto aquifer sediments was investigated in anaerobic laboratory batch and column uptake experiments and characterized by As, Fe, and Mn X-ray absorption spectroscopy (XAS) to estimate the extent and mechanism of abiotic sorption and oxidation of As(III). Batch experiments at pH 6 showed that the amount of As(III) or As(V) sorption from synthetic background porewater to sediments was similar as a function of total As concentration, but slightly more As(V) was sorbed than As(III) with increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 25 publications
1
18
0
1
Order By: Relevance
“…This increased the exposure of the activated sites on MnO 2 for As(III), and thus increasing its oxidation rate. Power et al (2005) confirmed competitive sorption of Zn 2+ on birnessite surfaces decreased the oxidation rate of As(III), and Choi et al (2009) also assumed competition between Fe(II) and As(III) for sorption sites on manganese oxides further blocked oxidation rate of As(III).…”
Section: Simultaneous Oxidation Of As(iii) and Fe(ii) By Mnomentioning
confidence: 66%
“…This increased the exposure of the activated sites on MnO 2 for As(III), and thus increasing its oxidation rate. Power et al (2005) confirmed competitive sorption of Zn 2+ on birnessite surfaces decreased the oxidation rate of As(III), and Choi et al (2009) also assumed competition between Fe(II) and As(III) for sorption sites on manganese oxides further blocked oxidation rate of As(III).…”
Section: Simultaneous Oxidation Of As(iii) and Fe(ii) By Mnomentioning
confidence: 66%
“…Geochemical simulation using the reaction progress approach to provide thermodynamic constraints (solubility and sorption) during changes from oxidized to reduced conditions, with model parameters generalized from field observations, lend insight into dynamic processes and factors that may control dissolved concentrations. Arsenic mobilization may occur in the zone affected by seasonal fluctuations of groundwater level potentially during two conditions: when ground water level rises, flooding reduced sediments and promoting oxidative dissolution of sulfide; and when water level falls and oxidized sediments become progressively reduced as microbial action consumes O 2 and other electron acceptors, reducing arsenic, iron, and manganese (the latter being particularly important in lowFe systems, e.g., Amirbahman et al, 2006;Choi et al, 2009). During an oxidative cycle, oxidation of iron and arsenic, leading to (co-)precipitation of Fe(III)-(hydr)oxides and arsenate and/or pH-controlled arsenate sorption, will be an effective attenuation mechanism as long as oxidative capacity is maintained and the ratio of arsenic to labile iron (and potentially manganese) is low.…”
Section: Discussionmentioning
confidence: 99%
“…Power et al [14] confirmed competitive sorption of Zn(II) on birnessite decreased the oxidation rate of As(III). Choi et al [36] assumed competition between Fe(II) and As(III) for sorption sites on manganese oxides further blocked the oxidation rate of As(III). Parikh et al [15] showed a reduced As(III) oxidation in the presence of phosphate (PO 4 3À ) caused by competitive adsorption between As(III) and PO 4 3À .…”
Section: Effects Of Fe(ii) On As(iii) Oxidationmentioning
confidence: 99%